Characterizing mild cognitive impairment in prodromal Parkinson's disease: A community‐based study in China. (25th November 2021) - Pan, Chenxi; Li, Yuqian; Ren, Jingru; Li, Lanting; Huang, Peiyu; Xu, Pingyi; Zhang, Li; Zhang, Wenbing; Zhang, Min‐Ming; Chen, Jiu; Liu, Weiguo
Abstract: Objective: The International Parkinson and Movement Disorder Society (MDS) has published research criteria for prodromal Parkinson's disease (pPD), which includes cognitive impairment as a prodromal marker. However, the clinical features of mild cognitive impairment (MCI) in pPD remain unknown. Our study aimed to evaluate the frequency and clinical features of mild cognitive impairment of pPD in the elderly in China. Methods: The cross‐sectional community‐based study recruited 2688 participants aged ≥50 years. Subjects were diagnosed with pPD according to the MDS criteria. Overall, 39 pPD and 22 healthy controls underwent comprehensive clinical and neuropsychological assessment. MCI was also diagnosed by the MDS criteria. Next, we investigated the relationship between clinical factors and cognition. Results: Among the 2, 663 dementia‐free and Parkinson disease (PD)‐free participants, 55 met the criteria for pPD (2.1%) and 23 pPD met the criteria for MCI. Memory, attention/working memory, and executive function were the most frequent impaired domains, and amnestic MCI multidomain phenotype was the most frequent MCI subtype (69.57%) in pPD. Additionally, correlation analysis revealed that the global cognitive performance was negatively related to UPDRS‐III score ( r  = −0.456, p  = 0.004). Conclusion: MCI, specifically impairment in memory, attention/working memory, and executive domain, is present at the prodromal stage of PD. In addition, cognitive performance is correlated with motor symptoms in pPD. Our results reflect that cognitive profile, combined with motor symptoms, can help clinicians to identify individuals with pPD early, as those would be the optimal candidates for neuroprotective therapy. Abstract : Mild cognitive impairment, specifically impairment in memory, attention/working memory, and executive, is present in prodromal PD in an elderly population of China. In addition, cognitive performance is correlated with motor symptoms in prodromal PD. The results reflect that cognitive profile, combined with motor symptoms, can help clinicians to identify individuals with prodromal PD early, as those would be the optimal candidates for neuroprotective therapy.